Shaping Tomorrow's Doctors: The Impact of Socioeconomic and Institutional Factors on Medical Education Quality in Brazil: An Ecological Study - Quécia H Fatel; Flávia GM Silva; Katia M Avena; Rodrigo C Menezes; Bruno B Andrade; Luiz F Quintanilha (Journal of Medical Education and Curricular Development)
Objectives Education holds transformative power in society, driving economic and social development. In medical education, training quality leads to well-prepared physicians and directly impacts patient care. In Brazil, a key measure of medical training quality is the National Student Performance Exam (Enade). This study aims to analyze the institutional, social, and economic determinants of the quality of medical education in Brazil through Enade scores. Methods An ecological study was conducted with all Brazilian higher education institutions participating in the Enade for the Medicine undergraduate course in the last 5 editions. Group comparisons and a multivariable logistic regression model were conducted to examine the associations between institutional, social, and economic aspects with the Enade score, categorizing institutions into high and low/medium score groups. Results Considering all editions, the average Enade score of medical schools in Brazil was 2.8. Geographic location was a determining factor of Enade results. The highest proportion of high scores was observed in South (62.4%) and Central-West (57.3%) regions, and low scores in the North (76.4%), Southeast (64.1%), and Northeast (52.6%). The proportion of medical schools with high Enade scores increased over time ( P  < .001), and they demonstrated significantly higher performance in general knowledge tests (+10.6%; 64.4 vs 58.20) and specific knowledge tests (+16.0%; 65.4 vs 56.4). Institutional factors associated with better student performance in Enade included a well-rated didactic-pedagogical organization (odds ratio [OR]: 1.62 [confidence interval (CI): 1.10-2.40]), a more qualified faculty (OR: 1.81 [CI: 1.27-2.59]), and being publicly administered (OR: 5.74 [CI: 3.44-9.95]). Conclusion This study highlights significant variations in training quality among medical schools nationwide, with the Center-South region showing a higher proportion of institutions achieving high Enade scores compared to more socioeconomically vulnerable regions in Brazil. Institutional characteristics such as well-rated didactic-pedagogical organization, a highly qualified faculty, and public administration are associated with better exam performance.